Schistosoma mansoni larvicidal activity of murine bronchoalveolar lavage cells. - Lewis, F A (1990)
We have investigated the ability of cells obtained from both normal and immune mice by bronchoalveolar lavage (BACs) to kill Schistosoma mansoni larvae in vitro. In cultures with mechanically derived schistosomules, high levels of larvicidal activity were displayed by BACs from both normal and irradiated cercaria-immunized C57BL/6 mice. Based on effector-to-target-cell ratios, BAC-mediated killing was two- to threefold more efficient than killing mediated by macrophage-rich cell populations obtained from the peritoneal cavity. BACs from normal A/J mice were essentially as larvicidal as normal C57BL/6 cells. However, BACs from a strain of mouse (P/J) with a known macrophage defect possessed negligible larvicidal activity. Macrophages made up 85 to 95% of BACs from all three strains tested. In contrast to cells of the IC-21 macrophage cell line, B6 BACs did not show enhanced killing activity when preincubated with lymphokine-containing supernatants. Lung schistosomules harvested 10 days after cercarial penetration were refractory to BAC-mediated killing.